Three‐Dimensional Modeling of the Ground Electric Field in Fennoscandia During the Halloween Geomagnetic Storm - Elena Marshalko; Mikhail Kruglyakov; Alexey Kuvshinov; Ari Viljanen (Space Weather)
Abstract In this study, we perform three‐dimensional (3‐D) ground electric field (GEF) modeling in Fennoscandia for three days of the Halloween geomagnetic storm (29–31 October 2003) using magnetic field data from the International Monitor for Auroral Geomagnetic Effects (IMAGE) magnetometer network and a 3‐D conductivity model of the region. To explore the influence of the inducing source model on 3‐D GEF simulations, we consider three different approaches to source approximation. Within the first two approaches, the source varies laterally, whereas in the third method, the GEF is calculated by implementing the time‐domain realization of the magnetotelluric intersite impedance method. We then compare GEF‐based geomagnetically induced current (GIC) with observations at the Mäntsälä natural gas pipeline recording point. We conclude that a high correlation between modeled and recorded GIC is observed for all considered approaches. The highest correlation is achieved when performing a 3‐D GEF simulation using a “conductivity‐based” laterally nonuniform inducing source. Our results also highlight the strong dependence of the GEF on the earth's conductivity distribution.